AN OVERVIEW OF THE HOTEL REVENUE MANAGEMENT MODELS - A. M. Bandalouski (Informatika)
The paper gives a brief scope of Hotel Revenue Management theory and discusses its basic def-initions. It also suggests a new classification of Revenue Management processes and surveys dynamic pricing, forecasting and optimization models employed in Hotel Revenue Management. Last section proposes promising directions of future research.